Molecular epidemiology, risk factors of zoonotic enteric protozoa and genetic diversity of Blastocystis infecting cattle in Peninsular Malaysia - Abdullah, Donea Abdulrazak (2017)
Enteric protozoa infections are one of the major constraints for profitable dairy and beef industries in tropical and subtropical countries, including Malaysia. Among the various economically important bovine diseases, enteric protozoan infections such as blastocystosis, cryptosporidiosis, giardiasis and buxtonellosis, are recognized as major causes of sub-clinical and clinical illness in cattle. In Malaysia, ruminant livestock farming is an important component of the agricultural sector, however there is a paucity of information on epidemiology and genetic diversity of enteric protozoa infecting cattle, especially those with zoonotic potential. In this study 824 faecal samples were collected from 39 cattle (beef and dairy) farms in different locations throughout Peninsular Malaysia. Genomic DNA was extracted from faecal samples and subjected to molecular detection of Cryptosporidium, Giardia, Blastocystis and Buxtonella using genus-specific primers. A high percentage (37.8%) of the cattle was infected with either one or more intestinal protozoa. Blastocystis was the most common (25.4%) enteric protozoa detected in the cattle, followed by Cryptosporidium (12.5%), Giardia (4.3%) and Buxtonella (2.7%). Double entric protozoa species coinfection was the most prevalent (4.7%), followed by triple species co-infection (0.7%). The most common (2.9%), and significantly corellated (rs=0.994; p<0.01) combination was Blastocystis + Cryptosporidium. Multivariable logistic regression shows that herd size, management system, production type, deworming frequency, and distance to water body were the risk factors associated with Blastocystis infection. For Cryptosporidium, deworming frequency, distance to human settlement, and management system were significant risk factors associated with the infection. Giardia infection was significantly associated with the cattle age, deworming frequency, zone and distance to human settlement, while risk factors for Buxtonella infection include herd size, distance to human settlement and deworming frequency. Positive amplicons of Blastocystis were cloned and sequenced to determine the genetic variability of the local Blastocystis isolates. Bioinformatics and phylogenetic analysis revealed the presence of ST1, ST3, ST5, ST10 and ST14 genotypes among the infected cattle. ST10 recorded the highest prevalence of 45.8%, follow by ST5 (37.4%). Of particular concern is the discovery of potentially human infective subtypes, namely ST1, ST3 and ST5. Although various subtypes were dominant among the animal and environmental based epidemiological parameters examined, there was no consistent pattern of prevalence. Similarly, the spatial distribution patterns did not exhibit a consistent pattern, as most of the genotypes were widespread throughout the country. There was a considerably high level of genetic variability among the Blastocystis subtypes whereby a total of 117 haplotypes were amplified, with high nucleotide diversity. The present study constitutes the first attempt to apply molecular detection techniques to determine epidemiological risk factors for enteric protozoa infections among cattle in Malaysia. It is also the first to genetically characterize the zoonotic Blastocystis protozoa among cattle in the country. The epidemiological and genotyping data obtained from this study will be beneficial for the control and prevention of zoonotic enteric protozoa among humans and ruminant livestock in the region.